Supervisi Akademik Kepala Sekolah Dan Komitmen Guru Terhadap Kinerja Guru Dalam Pembelajaran (Di Sdn Gugus Satu Kecamatan Rawas Ulu) - Masturo; Sumarsih; Putri Kartiwi, Asti (UNIVERSITAS BENGKULU, 2023)
The purpose of the study was to describe: 1) The effect of the principal's academic supervision on teacher performance in learning 2) The effect of teacher commitment on teacher performance in learning; 3) The influence of the principal's supervision and teacher commitment on teacher performance in learning. Quantitative research method with associative approach. Saturated sampling (census) is that all teachers are taken as a sample of 50 people. Data was obtained through research instruments in the form of questionnaires, and data processing using SPSS Vers.22. The results showed that: (1) there was a positive and significant influence of the principal's supervision on teacher performance in learning, this was proven by the t test. (2) there was a positive and significant influence of teacher commitment on teacher performance in learning, this was proven by the t test. (3) there is a positive and significant influence of the principal's supervision and teacher commitment to teacher performance in learning, this is evidenced by test F. From the results of the study, it is concluded that there is an influence of the principal's academic supervision and teacher commitment to teacher performance in learning at SDN cluster one Rawas Ulu District.